2007
DOI: 10.1037/0022-006x.75.6.864
|View full text |Cite
|
Sign up to set email alerts
|

Shapes of early change in psychotherapy under routine outpatient conditions.

Abstract: Although improvement of clients' state is a central concern for psychotherapy, relatively little is known about how change in outcome variables unfolds during psychotherapy. Client progress may follow highly variable temporal courses, and this variation in treatment courses may have important clinical implications. By analyzing treatment progress using growth mixture modeling up to the 6th session in a sample of 192 outpatients treated under routine clinic conditions, the authors identified 5 client groups bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
102
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 68 publications
16
102
1
Order By: Relevance
“…Participants who experience improvement may feel more inclined to track their progress and to make maximum use of the limited time available (12 weeks), whereas participants who show less early improvement may be discouraged from using the intervention more intensively. While early response is often associated with shorter treatment length [51], it has also already been reported that in time-limited treatment protocols, early response participants tend to complete the protocol and are less likely to drop out of treatment [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Participants who experience improvement may feel more inclined to track their progress and to make maximum use of the limited time available (12 weeks), whereas participants who show less early improvement may be discouraged from using the intervention more intensively. While early response is often associated with shorter treatment length [51], it has also already been reported that in time-limited treatment protocols, early response participants tend to complete the protocol and are less likely to drop out of treatment [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, researchers have indicated that early change in clients may be a powerful predictor of overall change, and a promising indicator of when treatment is working and when it is not (Stulz, Lutz, Leach, Lucock, & Barkham, 2007). However, achieving these converging clinical and research goals depends on reliable and valid measurement of clinical problems.…”
mentioning
confidence: 96%
“…On this basis, treatment response patterns can be detected. Specifically, growth mixture modeling (GMM) has been demonstrated to be useful for the identification of early change patterns (e.g., Cuijpers, van Lier, van Straten, & Donker, 2005;Lutz et al, 2014;Rubel, Lutz, & Schulte, 2013;Stulz, Lutz, Leach, Lucock, & Barkham, 2007). GMM is a latent variable cluster analytic method.…”
mentioning
confidence: 99%